Bahasa Inggris: Bahasa Indonesia - I Desak Putu Diah Anggiani; Budi Irmawati; Royana Afwani (Journal of Computer Science and Informatics Engineering (J-Cosine), 2025)
The development of a web-based Scout Information System for Kwartir Cabang Mataram aims to improve the management of member data and activities through a REST API. The current data management process, relying on tools like Google Forms and Microsoft Excel, is inefficient and error-prone. To address these issues, the proposed system integrates all levels of scout organization within the Mataram City, from school-based scout units (gugus depan) to the city level scout organization (kwartir cabang), creating a centralized platform for real-time data access. Built using the Scrum method, the system is developed through iterative sprints and regularly improved based on stakeholder feedback. The REST API architecture enables seamless communication between the back-end and front-end components, ensuring system scalability, flexibility, and future integration with other platforms, including mobile applications. Black-box testing guarantees the functionality of the system’s endpoints. This system is expected to enhance operational efficiency and reduce administrative delays.